2019
DOI: 10.3892/br.2019.1200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging on the tendon structure and tendon‑associated gene expression in mouse foot flexor tendon

Abstract: To evaluate the biological changes in tendons during the aging process, the present study examined the effect of aging on the tendon structure, distribution of collagen types I and III, and expression of tendon-associated genes, using flexor tendons in a mouse model. Histological assessment of the tendon structure and distribution of collagen types I and III were performed, and the expression of tendon-associated genes was evaluated in flexor digitorium longus tendons of young (8 weeks) and aged (78 weeks) fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 37 publications
(43 reference statements)
6
26
0
Order By: Relevance
“…Bgn, Dcn, Eln, and Fbn1 as components of ECM were also downregulated in old HCR and old LCR. Downregulation of collagens due to age is consistent with previous findings in the flexor tendons of mice [18] and in the Achilles and tibialis anterior tendons of rats [22]. However, Yu.…”
Section: Discussionsupporting
confidence: 91%
“…Bgn, Dcn, Eln, and Fbn1 as components of ECM were also downregulated in old HCR and old LCR. Downregulation of collagens due to age is consistent with previous findings in the flexor tendons of mice [18] and in the Achilles and tibialis anterior tendons of rats [22]. However, Yu.…”
Section: Discussionsupporting
confidence: 91%
“…Selecting C57BL/6J mice older than 24 months is not advisable because of the increased prevalence of age-specific disease that could lead to confounding results [52,53]. 18-22-month-old C57BL/6J mice have also been published as "old" age groups in multiple tissue types, including the lung, gut, spleen, skin, ovaries, eyes, brain, nails, tendon, meniscus, cartilage, bone, and skeletal muscle [42,[54][55][56][57][58][59][60][61][62]. Additionally, senescence-like changes, a marker of old age, are observed between 18 and 24 months in C57BL/6J mice [54,[63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…Because PSR molecules align parallel to the long axis of each collagen fiber, PSR enhances the birefringence of collagen under polarized light microscopy. 17,21,22 In addition to detecting bulk collagen, PSR staining has been used to distinguish collagen type I from collagen type III in several tissues, such as those of the musculoskeletal system, [23][24][25] liver, 26 gastrointestinal tract, 27 skin, 28,29 and myocardium. 30 With visualization of PSRstained tissues under polarized light, termed PSRpolarization, thick collagen type I fibers appear yellowish-orange, orange, to red, whereas thin collagen type III fibers are supposed to appear green to yellowish-green against a black background.…”
Section: Introductionmentioning
confidence: 99%
“…30 With visualization of PSRstained tissues under polarized light, termed PSRpolarization, thick collagen type I fibers appear yellowish-orange, orange, to red, whereas thin collagen type III fibers are supposed to appear green to yellowish-green against a black background. 23,31 Although many studies have confirmed that PSR staining is useful for studying the collagen network under normal conditions and in pathological processes in different tissues, [23][24][25][26][27][28]32,33 other studies have questioned whether this staining can identify collagen types by their colors under polarized light. 29,[34][35][36] For instance, one study using PSR-stained skin sections from patients with Ehlers-Danlos syndrome type IV showed fibers displaying the birefringence of collagen type III (greenish), although this condition is characterized by collagen type III deficiency.…”
Section: Introductionmentioning
confidence: 99%